Intendiranost Huserlove fenomenologije Descartesovom kogitacijom / The Intentionality of Husserl's Phenomenology by Cartesian Cogitation - Karović, Jasenko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
This paper analyzes the relation between Descartes' Cogito theory and Husserl's phenomenology. In other words, it deals with the influence of rationalist philosophy on phenomenology as one of the most important modern philosophy’s epistemology concepts. After applying his epochal discovery, embraced in the syntagm cogito ergo sum, to the entire cognitive horizon, Descartes left the objective, external world and permanently placed epistemology in the area of that inner world which is different from its original notion because of undergoing the change by that intentional, creative, transcendental factor. The epistemology is no longer interested in objective world but phenomena that Husserl’s method furthermore puts into the process of reduction, called phenomenological epoché which is supposed to lead us backwards, to the object itself as the way of knowledge. Husserl succeeded in developing the original ego cogito into ego cogito cogitatum. The author demonstrates the real intentionality of Husserl's phenomenology by using that critic aspect of Descartes cogito theory as well as current position of phenomenology in epistemic history from its foundation of knowledge.